Diabetes management in OLDES project - Novák, Daniel; Uller, Miroslav; Rousseaux, S; Mráz, Miloš; Smrž, Jan; Štěpánková, Olga; Haluzík, Martin; Busuoli, Massimo (Conference proceedings ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2009)
EU project OLDES (Older People's e-services at home) develops easy to use and low cost ICT platform in order to offer a better quality of life to elderly people directly in their homes through innovative systems of tele-accompany, tele-assistance and tele-medicine. The elderly are able to access the services and send relevant medical data from their home by being connected to the central server via a low cost PC which is based on Negroponte paradigm. The OLDES platform interface uses television screens controlled through a remote control customized for the elderly. The feasibility of OLDES project is evaluated by the pilot study concentrating on compensation of diabetic patients. Compensation of diabetes is achieved by monitoring glucose glycemia level, blood pressure and weight. Moreover, the patient feeds into OLDES system daily consumption of food using interactive food scales and obtains advice if necessary.
Keywords: Telemedicine; biomedicínské inženýrství; uživatelské rozhraní počítače; služby domácí péče; Home Care Services; diabetes mellitus; lidé; Evropská unie; zdravotní služby pro seniory; mikropočítače; Pilot Projects; telemedicína; pilotní projekty; Aged; Microcomputers; European Union; Health Services for the Aged; Biomedical Engineering; Diabetes Mellitus; senioři; User-Computer Interface; Humans